Agenesia dental : Revisión bibliográfica y reporte de dos casos clínicos (2006)
ABSTRACT: Tooth agenesis is the most common anomaly of craniofacial development. The purpose of this report is to present a brief review of literature about tooth agenesis, which includes: terminology, etiology, prevalence, associated syndromes and dental anomalies. Two clinical cases are presented. In Colombia there are no studies which allow us to determine the genetic causes of this anomaly, more research is needed in this area in order to clarify its etiology.